TEACHING STUDENTSâ€™ FRICATIVE PRONUNCIATION THROUGH TONGUE TWISTER TECHNIQU - Awista, Awista; Ikhsanuddin, Ikhsanudin; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was aimed at finding out whether or not tongue twister technique has significant effects in teaching fricative pronunciation of year-8 students of SMP Kartika XVII-01 Sungai Raya. The population of this research is the Year-8 students of SMP Kartika XVII-01 Sungai Raya in academic year 2018/2019. The sample of this research consists of 20 students which are chosen by using cluster random sampling. This research is pre-experimental research with pretest, posttest and two times of treatments. The finding of this research showed that mean score of the studentsâ€™ pre-test is 50 while the post-test is 58. The tratio is higher than the tcritical (5.33 > 2.093). The result of the effect size (ES) is 1.17. It showed that null hypothesis â€œtongue twister technique does not affect studentsâ€™ fricative pronunciationâ€ is rejected and the alternative hypothesis â€œtongue twister affects studentsâ€™ fricative pronunciationâ€ is accepted. It proves that tongue twister technique has significant effect in teaching studentsâ€™ fricative pronunciation, especially sound [Êƒ]. Therefore, based on the studentsâ€™ achievement, the writer recommends English teachers to apply tongue twister technique as a part of their pronunciation teaching.Â Keywords: Pronunciation, Fricative, Tongue Twister Technique